U.S. and Chilean College Students' Reading Practices: A Cross‐Cultural Perspective. Issue 4 (31st March 2016) - Huang, Suhua; Orellana, Pelusa; Capps, Matthew
Abstract: The purpose of this study was to investigate the differences between the amounts of time that U.S. and Chilean students spend on conventional academic reading, extracurricular reading, and Facebook and also to report the types of materials they prefer to read. The study surveyed students in the United States ( n = 1, 265) and Chile ( n = 2, 076) across all discipline areas. Descriptive analysis indicated that U.S. students spent 4.94 hours on academic reading, 4.17 hours on extracurricular reading, and 16.40 hours on Facebook weekly. For Chilean students, the figures were 13.17 hours, 3.07 hours, and 14.00 hours, respectively. The results indicated that for both U.S. and Chilean participants, online reading materials were the most popular type of material, followed by magazines/newspapers, graphic novels/comic books, best‐selling novels, and nonmajor academic books (books on topics outside the student's major subject in conventional print format). Due to the impact of the Internet on reading resources, students' reading patterns today are different from how they were in the past. College students' reading practices have moved to different venues with the advent of Internet technology, and the modality has migrated to online reading. Specifically, social media sites (e.g., Facebook) provide social accessibility to academic contexts that constitute students' learning experiences and shape their identities.